Genética na escola - Carnímeo, Eduardo Sávio Gomes [UNESP]; Giorgenon, Carlos Henrique Braz [UNESP]; Silva, Flávia Alves Marques da [UNESP]; Revolti, Lucas Tadeu Mazza [UNESP]; Amaral, Camila Baptista do [UNESP]; Marconato, Marcela Bonafin [UNESP]; Dutra, Sophia Mangussi Franchi [UNESP]; Buzinaro, Rodolfo [UNESP]; Oliveira, Gustavo Hugo Ferreira de [UNESP]; Môro, Gustavo Vitti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Humans has always been interested in genetics for many years, and their study is very important for developing better plants and animals. In 2008 it was added to the curriculum of the Brazilian high school some issues about genetics. Unesp of Jaboticabal has several courses in which genetics is a compulsory subject. For this reason, the project Genetics at School was developed to transmit practical knowledge of genetic to third year high school students. The topics covered for the classes will be: reproduction of the species (sexual and asexual), heredity, Mendel's laws, sex-linked inheritance, blood incompatibility groups, genetic code: DNA and RNA, paternity tests (electrophoresis), biotechnology and genetically modified organisms, genetic improvement and "general curiosities", being taught through classes with the aid of powerpoint and other resources. During the first half, as well as preparation of lessons and teaching materials, schools consultation was made to check availability and interest, and these four signaled positively. In the second half the lessons related to the proposed topics will be taught from September.

O homem sempre se interessou pela genética desde muitos anos, e seu estudo é muito importante para desenvolvimento de plantas e animais melhores. No ano de 2008 foi adicionado ao currículo do ensino médio brasileiro alguns assuntos sobre genética. A Unesp de Jaboticabal possui vários cursos em que genética é disciplina obrigatória. Por esse motivo, foi elaborado o projeto Genética na Escola para transmitir conhecimentos práticos da área aos alunos do terceiro ano do ensino médio. Os temas abordados para as aulas serão: reprodução das espécies (sexuada e assexuada), hereditariedade, Leis de Mendel, herança ligada ao sexo, grupos sanguíneos e incompatibilidade, código genético: DNA e RNA, testes de paternidades (eletroforese), biotecnologia e os organismos geneticamente modificados, melhoramento genético e "curiosidades gerais", sendo ministrado por meio de aulas com auxílio de Datashow e outros recursos. Durante o primeiro semestre, além da elaboração das aulas e materiais didáticos, foi feita consulta às escolas para verificar interesse e disponibilidade e, destas, quatro sinalizaram positivamente. No segundo semestre serão ministradas as aulas referente aos temas propostos, a partir de setembro.
Keywords: Education; Jaboticabal; Biology; Ensino; Jaboticabal; Biologia